The Impact of Electricity Competitive Market Establishment on Technical Efficiency of Thermal Power Plants in Iran - Motafakker Azad, Mohammad Ali; Pourebadollahan Covich, Mohsen; Sojoodi, Sakineh (International Journal of Energy Economics and Policy, 2015)
Power industry like other network industries, due to economies of scale, has monopolistic operation for many years. Over the last three decades, electricity sectors in most countries have experienced major structural changes including entry of private capital and competition increase. Although the effects of such reforms in developed economies are now well documented, in developing countries, a few studies have examined the effects of these changes due to a variety of reasons. In Iran, structural problem is one of the main problems in the energy sector, which has had an important role in low efficiency of this sector. To solve this problem, in two past decades, restructuring and promoting competition have been in the forefront of government policy and programs in the energy sector. So that substantial reforms occurred in electricity industry structure after establishing power market in 2003. After a decade of reforms in power market, it is necessary to investigate the effects of these reforms on electricity supplier performance, since it will be helpful for progress of electricity industry restructuring and implementing similar reforms in other network industries. The aim of this study, given its real importance in the issue, is examining the effects of market restructuring on technical efficiency in thermal power plants of Iran. For this purpose, technical efficiency of 35 thermal power plants has been calculated in the period 1999 to 2011 using DEA method, then the impact of market restructuring on technical efficiency has been estimated by applying Panel Data Tobit model. The results indicated that market restructuring has had positive effects on technical efficiency of power plants. Keywords: Electricity Industry; Market Restructuring; Technical Efficiency; Thermal power plants; Panel Data Tobit. JEL Classifications: C14; C51; C61; D24; L33; L51; L94